Pharmacokinetics, Pharmacodynamics and Safety of Febuxostat, a Non-Purine Selective Inhibitor of Xanthine Oxidase, in a Dose Escalation Study in Healthy Subjects - Khosravan, Reza; Grabowski, Brian A; Wu, Jing-Tao; Joseph-Ridge, Nancy; Vernillet, Laurent (Clinical pharmacokinetics, 2006)
Febuxostat is a novel non-purine selective inhibitor of xanthine oxidase currently being developed for the management of hyperuricemia in patients with gout. To investigate the pharmacokinetics, pharmacodynamics and safety of febuxostat over a range of oral doses in healthy subjects. In a phase I, dose-escalation study, febuxostat was studied in dose groups (10, 20, 30, 40, 50, 70, 90, 120, 160, 180 and 240 mg) of 12 subjects each (10 febuxostat plus 2 placebo). In all groups, subjects were confined for 17 days and were administered febuxostat once daily on day 1, and days 3-14. During the course of the study, blood and urine samples were collected to assess the pharmacokinetics of febuxostat and its metabolites, and its pharmacodynamic effects on uric acid, xanthine and hypoxanthine concentrations after both single and multiple dose administration. Safety measurements were also obtained during the study. Orally administered febuxostat was rapidly absorbed with a median time to reach maximum plasma concentration following drug administration of 0.5-1.3 hours. The pharmacokinetics of febuxostat were not time dependent (day 14 vs day 1) and remained linear within the 10-120 mg dose range, with a mean apparent total clearance of 10-12 L/h and an apparent volume of distribution at steady state of 33-64 L. The harmonic mean elimination half-life of febuxostat ranged from 1.3 to 15.8 hours. The increase in the area under the plasma concentration-time curve of febuxostat at doses >120 mg appeared to be greater than dose proportional, while the febuxostat maximum plasma drug concentration was dose proportional across all the doses studied. Based on the urinary data, febuxostat appeared to be metabolised via glucuronidation (22-44% of the dose) and oxidation (2-8%) with only 1-6% of the dose being excreted unchanged via the kidneys. Febuxostat resulted in significant decreases in serum and urinary uric acid concentrations and increases in serum and urinary xanthine concentrations. The percentage decrease in serum uric acid concentrations ranged from 27% to 76% (net change: 1.34-3.88 mg/dL) for all doses and was dose linear for the 10-120 mg/day dosage range. The majority of adverse events were mild-to-moderate in intensity. Febuxostat was well tolerated at once-daily doses of 10-240 mg. There appeared to be a linear pharmacokinetic and dose-response (percentage decrease in serum uric acid) relationship for febuxostat dosages within the 10-120 mg range. Febuxostat was extensively metabolised and renal function did not seem to play an important role in its elimination from the body.